How Can Prosocial Behavior Be Motivated? The Different Roles of Moral Judgment, Moral Elevation, and Moral Identity Among the Young Chinese - Ding, Wan; Shao, Yanhong; Sun, Binghai; Xie, Ruibo; Li, Weijian; Wang, Xiaozhen (Frontiers in Psychology, 2018)
Prior research has shown that moral judgment, moral elevation, and moral identity contribute to prosocial behavior. However, how the three motivating factors interact in predicting prosocial behaviors is not yet clear. The current study proposed and examined a moderated mediation model to illustrate the specific process how prosocial behavior is motivated by these factors. A total of 264 Chinese undergraduate and graduate students participated in the present study (140 females; 17–26 years, M = 20.25, SD = 1.57). Moral judgment competence, intensity of moral elevation, and moral identity of participants were measured by self-reported scales, and the tendency to engage in prosocial behavior were assessed in the simulated “Ask for help” situation. The results showed that moral elevation mediated the effect of moral judgment on prosocial behavior, and moral identity moderated this mediation through interacting with moral elevation. Results supported the assumptive model and provided a comprehensive framework to explain prosocial behavior. However, within the proposed model, the mediating effect of moral elevation in women was stronger than in men, and the moderating role of moral identity appear in women, but not in men. These findings imply different methods for men and women to enhance their prosocial behaviors, including that more attention to developing moral reasoning should be paid in men, while more emphasis on evoking moral emotion and moral traits should be put in women.